Generating interstitial water within the persisting tetrahedral H-bond network explains density increase upon compressing liquid water - Förster, Mirko; Ukoji, Nnanna; Sahle, Christoph J.; Niskanen, Johannes; Sakrowski, Robin; Surmeier, Göran; Weis, Christopher; Irifune, Tetsuo; Imoto, Sho; Yavas, Hasan; Huotari, Simo; Marx, Dominik; et al. (National Academy of Sciences, 2025)
Despite its ubiquitous nature, the atomic structure of water in its liquid state is still controversially debated. We use a combination of X-ray Raman scattering spectroscopy in conjunction with ab initio and path integral molecular dynamics simulations to study the local atomic and electronic structure of water under high pressure conditions. Systematically increasing fingerprints of non-hydrogen-bonded H2O molecules in the first hydration shell are identified in the experimental and computational oxygen K-edge excitation spectra. This provides evidence for a compaction mechanism in terms of a continuous collapse of the second hydration shell with increasing pressure via generation of interstitial water within locally tetrahedral hydrogen-bonding environments.